2008
DOI: 10.1007/s11136-008-9322-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French version of the colorectal-specific quality-of-life questionnaires EORTC QLQ-CR38 and FACT-C

Abstract: This study confirms the value of the FACT-C and suggests some limits of the QLQ-CR38 for patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…From the above results and literature, it can be seen that the psychometric properties of this instrument are very similar to those of the original English version and other language versions [4,6,11,12]. For example, the original English version of QLQ-CR38 showed that Cronbach’s α coefficients for seven of the nine scales exceeded the 0.70 criterion at one or both assessments, the test-retest reliability for all scales and a single item was 0.78 or higher, and selective scales detected change over time as a function of change in the performance status and treatment-induced change.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…From the above results and literature, it can be seen that the psychometric properties of this instrument are very similar to those of the original English version and other language versions [4,6,11,12]. For example, the original English version of QLQ-CR38 showed that Cronbach’s α coefficients for seven of the nine scales exceeded the 0.70 criterion at one or both assessments, the test-retest reliability for all scales and a single item was 0.78 or higher, and selective scales detected change over time as a function of change in the performance status and treatment-induced change.…”
Section: Discussionsupporting
confidence: 57%
“…It also showed that only the role functioning/physical score was slightly higher in the laparoscopic cholecystectomy group (p = 0.038) [23]. Therefore, more cancer-specific QOL instruments were developed including QLQ-CR38 [4,6,11,12], FACT-C [5,14], and QLICP-CR [15,16] for patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations